Подвійне променезаломлення вакууму в полі кільця зі струмом та направленої електромагнітної хвилі - Novak, O.; Diachenko, M.; Padusenko, E.; Kholodov, R. (Publishing house "Academperiodika", 2018)
The vacuum birefringence effect in magnetic fields generated by either a laser-driven capacitor-coil generator or an electromagnetic wave in a radio frequency guide has been theoretically studied. The ellipticity acquired by a linearly polarized laser beam propagating in those fields is calculated. The obtained results are compared with the parameters of the PVLAS experiment aimed at the experimental observation of the vacuum birefringence effect in a magnetic field.